2014
DOI: 10.1016/j.geomphys.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Cramer varieties Cr(r,r+s,s)

Abstract: Abstract. In this paper we study quasi-homogeneous affine algebraic varieties, that is, varieties obtained as closures of orbits of suitable group representations. We also discuss one interesting case that has links with the Orthogonal Grassmannian OGr(5, 10). The main aim is to write the tangent bundle and the canonical class of quasi-homogeneous affine algebraic varieties in terms of group representations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Equivalently, a homogeneous space is of the form G/H, where G is an algebraic group and H a closed subgroup of G. Homogeneous spaces play a vital role in the representation theory of the algebraic group because representations are often realised as the space of sections of vector bundles over homogeneous spaces. Many authors [2,3,4,5,6] have studied homogeneous and quasi-homogeneous spaces in different contexts. Corti and Reid [1] studied weighted analogs of the homogeneous spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Equivalently, a homogeneous space is of the form G/H, where G is an algebraic group and H a closed subgroup of G. Homogeneous spaces play a vital role in the representation theory of the algebraic group because representations are often realised as the space of sections of vector bundles over homogeneous spaces. Many authors [2,3,4,5,6] have studied homogeneous and quasi-homogeneous spaces in different contexts. Corti and Reid [1] studied weighted analogs of the homogeneous spaces.…”
Section: Introductionmentioning
confidence: 99%
“…A marked change in the phenotype is characterized by DCM heart, triggered by endothelial dysfunction, perturbed metabolic regulation, and altered cell signaling pathways. [14] Recently, we have shown that DCM rat heart exhibits higher sensitivity of I/R-associated cardiac injury than DM heart. [15] Besides, we demonstrated that cardiac mitochondrial dysfunction plays a vital role in the pathology of DCM heart.…”
mentioning
confidence: 99%